2019
DOI: 10.1021/acs.energyfuels.8b04042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Growth Kinetics of Tetra-n-butylammonium Bromide Hydrate Formation in Small Spaces

Abstract: Kinetics of tetra-n-butylammonium bromide (TBAB) hydrate formation orientated within the space of a small dimension tube is investigated through microscopic experiments in the temperature range-5.5 o C to-9.7 o C. Based on the experimental data, a kinetic model in small dimensional space is proposed to describe formation process. Hydrate crystals are observed uniformly growing in small dimensional space. The experimental results show that the nucleation time of TBAB hydrate increases from 9 min to 25 min and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Figure a shows the nucleation and growth process of the TBAB hydrate on a Cu substrate, a GF-2200, and a PF/ZSM-5 coating. Raman spectra (Figure S11) confirmed that the crystal formed by TBAB solution below the ice point was a hydrate . TBAB hydrate easily nucleated at the Cu surface, and the appearance of TBAB hydrate was table-like crystals .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Figure a shows the nucleation and growth process of the TBAB hydrate on a Cu substrate, a GF-2200, and a PF/ZSM-5 coating. Raman spectra (Figure S11) confirmed that the crystal formed by TBAB solution below the ice point was a hydrate . TBAB hydrate easily nucleated at the Cu surface, and the appearance of TBAB hydrate was table-like crystals .…”
Section: Resultsmentioning
confidence: 90%
“…Afterward, the temperature was heated to 15 °C to decompose the TBAB hydrate. After the decomposition, the temperature was lowered to −10 °C (Δ T sub = 21 °C) until the hydrate began to nucleate and grow again and then rapidly heated up to 3 °C to ensure that the hydrate was pure and free of ice . Before starting the adhesion measurement, the TBAB hydrate was annealed at 3 °C for 30 min to ensure its complete transformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last ten years, various characteristics and factors affecting the efficiency of the TBAB hydrates application in the cooling systems have been studied. The study of the kinetics of formation/decomposition of ICHs is necessary for the design of the cold storage and transportation facilities and optimization of their parameters. The growth kinetics equations and the mathematical model of TBAB hydrate formation were obtained by studying the growth kinetics of TBAB crystals in a small spatial volume . The study of the kinetics of TBAB hydrate formation using electrical resistance measurements and an artificial neural network model revealed that the main factors that influence the kinetic characteristics of TBAB hydrate formation are the TBAB solution concentration, the temperature, and the seed type .…”
Section: Introductionmentioning
confidence: 99%
“…The growth kinetics equations and the mathematical model of TBAB hydrate formation were obtained by studying the growth kinetics of TBAB crystals in a small spatial volume. 34 The study of the kinetics of TBAB hydrate formation using electrical resistance measurements and an artificial neural network model revealed that the main factors that influence the kinetic characteristics of TBAB hydrate formation are the TBAB solution concentration, the temperature, and the seed type. 35 Another potential application of TBAB hydrate formation for desalination of produced water has recently been proposed; 36 however, it is disputed 37,38 and might require further study.…”
Section: Introductionmentioning
confidence: 99%